EFFECT OF ACIDITY CHANGES ON MOBILITY OF METALLIC TRACE ELEMENETS IN MAIPO RIVER SEDIMENTS - Sylvia Violeta Copaja; Sylvia Copaja; Gabriel Arriagada (Journal of the Chilean Chemical Society, 2024)
The mobility and availability of metallic trace elements in river sediments depends on their solubility and adsorption on colloidal fraction of sediment. Processes such as cation exchange, adsorption/desorption, precipitation/dissolution and complexation affects the distribution of metals between the water column and sediments, being responsible for their mobility and availability. Trace elements in sediments are retained in the matrix, the concentration of the soluble fraction is scarce, this depending both on the physical and chemical properties of the sediment and the nature of metal.In this work we studied the effect of pH on the solubility of metallic trace elements in river sediments in order to evaluate their mobility into the water column.Samples were collected in 3 sites of Maipo River basins: Angostura (Ang), Clarillo (Cla) and Puangue (Pu) recording sites by GPS coordinates. The sediments were characterized: pH, electric conductivity (EC), soluble organic carbon (SOC), total organic carbon (TOC), available P, carbonate and Mn, Al Fe oxides.For determination of trace elements in total fraction in sediment, samples 0.25 mg, were digested in a microwave oven and determined by AAS. To study pH effect in release of metal mass of 2.5 g sediment was stirred for 24 h with 15 mL of solutions at pH 5.0; 4.0; 3.0; 2.0, which were prepared with nitric acid. Then all the samples were centrifuged, filtered and the respective metals measured by AAS.The content of total metals indicates that the major metals on the 3 sites were Al and Fe , Pu site presents the lowest concentrations of these two metals, Zn, Cu and Mn are higher in Pu, Mn concentration in Pu is three times higher than Cla and Ang. Mo was not detected.At pH = 2, the highest mobility was obtained according to the recoveries obtained. At pH 3, 4, 5 heavy metals are not mobilized or are obtained with very low recovery percentages. In all cases was Pu which presented the lowest recovery rates. Only Mn represents values of RAC with indicates high risk in Cla and Ang